PRODUKTIVITAS TANAMAN Asystasia gangetica (L.) Subsp. Micrantha YANG DIBERI PUPUK NPK DISUBSTITUSI DENGAN BIOURIN SAPI - N. G. K., RONI; LINDAWATI, S. A.; DEWI, P. J. N. (Fakultas Peternakan Universitas Udayana, 2024)
The research aims to obtain a dose of NPK fertilizer substituted for cow biourine that can produce the best productivity of Asystasia gangetica (L.) subsp. Micrantha, used a completely randomized design consisting of 9 tre- atments repeated 7 times, so there were 63 experimental units. Treatments consisted of D0: no fertilizer, D1: NPK 200 kg ha-1, D2: Cow biourine (CB) 5,000 l ha-1, D3: CB 7,500 l ha-1, D4: CB 10,000 l ha-1, D5: NPK 50 kgha-1 + CB 5,000 l ha-1, D6 : NPK 50 kgha-1 + CB 7,500 l ha-1, D7 : NPK 100 kgha-1 + CB 5,000 l ha-1, and D8 : NPK 100 kgha-1 + CB 7,500 l ha-1. The results showed that Asystasia gangetica that received the D5 treatment produced a higher number of leaves, leaf dry weight, stem dry weight, and total forage dry weight compared to D0 and the same as the D1 treatment. It was concluded that Asystasia gangetica (l.) subsp. Micrantha that received D5 fertilizer treatment (NPK 50 kgha-1 + cow biourine 5,000 l ha-1) showed better growth and yield compared to without fertilizer and the same as D1 treatment (NPK 200 kg ha-1).